Answer:
Option B: (x= -8, y=10, z=-6)
Explanation:
2x + 4y + 3z = 6 ... eq.(1)
5x + 8y + 6z = 4 ... eq.(2)
4x + 5y + 2z = 6 ... eq.(3)
From eq.(1),
2x= 6 - 4y - 3z
x= (6-4y-3z)/2 ... eq.(4)
Putting x as (6-4y-3z)/2 in both eq.(2) and eq.(3)
In eq.(2),
5[(6-4y-3z)/2] +8y +6z =4
Multiplying through by 2
5(6-4y-3z) + 16y + 12z = 8
30-20y-15z+16y+12z = 8
22= 4y + 3z ... eq(5)
In eq.(3),
4[(6-4y-3z)/2] +5y +2z = 6
2(6-4y-3z) +5y + 2z =6
12-8y-6z + 5y +2z = 6
6= 3y + 4z ... eq.(6)
Multiplying eq.(5) and eq.(6) by 3 & 4 respectively
66=12y + 9z ... eq(8)
24=12y + 16z ... eq(9)
Subtracting eq(8) from eq(9)
42= -7z
z= -42/7
z = -6
Putting z as -6 in eq.(5)
22= 4y + 3(-6)
22= 4y -18
4y = 40
y = 40/4
y = 10
Putting y as 10 and z as -6 in eq(4)
x = [6 - 4(10) - 3(-6)]/2
x = (6 - 40 - 18)/2
x = -16/2
x = -8
x= -8, y= 10 , z= -6